2021
DOI: 10.1002/ajim.23257
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma: Ongoing controversies about its etiology in females

Abstract: Malignant mesothelioma (MM) is one of the most aggressive cancers with the poorest of outcomes. There is no doubt that mesothelioma in males is related to asbestos exposure, but some authors suggest that most of the cases diagnosed in females are “idiopathic.” In our assessment of the science, the “low risk” of mesothelioma in females is because of the nonsystematic recording of exposure histories among females. Indeed, asbestos exposure is mentioned in only some of the studies that include females. We estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…However, the AF related to non-occupational exposures is higher in women [ 8 ]. The lower AF in women is partly due to an inadequate capture of exposure histories caused by lack of knowledge about previous exposure rather than due to biological differences [ 9 , 10 ]. In fact, most studies on the effect of asbestos have been performed in sectors with a predominance of male workers; it was only in recent years that patterns of asbestos exposure have been demonstrated in other industries (e.g., the textile industry, in which women were the majority employed and affected) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the AF related to non-occupational exposures is higher in women [ 8 ]. The lower AF in women is partly due to an inadequate capture of exposure histories caused by lack of knowledge about previous exposure rather than due to biological differences [ 9 , 10 ]. In fact, most studies on the effect of asbestos have been performed in sectors with a predominance of male workers; it was only in recent years that patterns of asbestos exposure have been demonstrated in other industries (e.g., the textile industry, in which women were the majority employed and affected) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women may have a higher prevalence of familial asbestos exposure (when a member of their family has occupational exposure to asbestos) [42][43][44][45]. A study suggested that the risk of MM in females is comparable to that of males, and more thorough exposure histories for females are required [46].…”
Section: Discussionmentioning
confidence: 99%
“…However as Baur et al point out, misclassification or inadequate exposure ascertainment has led to this low attributable risk for women compared to men. [16]. Data from occupationally exposed cohorts that included men and women actually show that compared to similarly exposed men, women had higher mortality rates from mesothelioma [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%